Empirical Study on the Driving Force of Urban Utility Tunnel Development - Yang Wang; Lang Liu (Salehan Institute of Higher Education, 2019)
Urban utility tunnel has been regarded as an important symbol of urban modernization, so it is important to understand the quantized relationship between city development and urban utility tunnel for city management and policy making. In this study, the internal relationship between the development amount of urban utility tunnel and urban population density was discussed, as well as urban GDP per capita, urban construction land area per capita and urban land price index, based on the IBM SPSS platform, through adopting the development amount of urban utility tunnel and the urban development data of the past 46 years of Japan. It was shown that the correlation relationship of the development amount of urban utility tunnel with the density of urban population was comparatively strong negative, and relatively strong positive, comparatively strong positive, relatively strong negative for GDP per capita, urban construction land area per capita and urban land price index respectively, which explained the driving effect that urban development imposed on urban utility tunnel construction in essence. Furthermore, a quantitative model was proposed for the relationship between the development amount of urban utility tunnel and urban development indexes, and the model could be a reference for decision making of urban utility tunnel development in China and other countries.